Is cranial restriction in infants with hydrocephalus a useful method to increase the effectiveness of endoscopic third ventriculostomy? - Salerno, María Cecilia; Colombo, Gonzalo; Tello Brogiolo, Nicolás; Maldonado Alejos, Carolina; Hinojosa, Lucas; Emmerich, Juan Pablo (Revista Argentina de Neurocirugía, 2025)
Background: endoscopic third ventriculostomy (ETV) is a well-established neurosurgical procedure for the treatment of hydrocephalus. It has been describe a variable success rate with more failures in patients under one year old. A few theories try to explain why there are more failures in these patients: one of them suggests that the presence of a distensible skull could be the main cause. Objectives: to analyze the success rate of placing a containment band in infants after an ETV. Methods: a retrospective-descriptive study was performed, between January 2018 and December 2020. We included patients less than one year old treated with hydrocephalus that was treated with an ETV. All of them were placed a contention band immediately after surgery. An analysis of the demographic data, the surgical procedure and the success rate was performed. Results: twenty-four patients were included, 58.3% were male. The medium age was 1.5 months old. Most of the patients has a pos-hemorragic hydrocephalus (n=14). The global success rate was 41.6%. The ETV success score was ≥40 in 54.2 % of the patients, 29.2% had score of 30, and 16.6% score of 20. Conclusion: ETV is an efficient procedure for the treatment of infants with hydroceophalus, having a variable success rate. In our series the implementation of a contention band on infants did not improve the success rate of ETV.